2017
DOI: 10.1055/s-0043-115384
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality indicators among nurse practitioners performing upper endoscopy

Abstract: Background and study aims  Limited international data have shown that non-physicians can safely perform upper endoscopy, but no such study has been performed in the United States. Our aim was to assess the quality of outpatient upper endoscopies performed by nurse practitioners (NPs). Patients and methods  Retrospective chart review of upper endoscopies performed by 3 NPs between 2010 and 2013 was performed. Comparisons among all NPs performing upper endoscopy and assessment of individual NP performance over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In a national survey of pediatric surgeons, nearly all respondents endorsed that integration of APPs in inpatient and outpatient settings positively impacted care, particularly with regard to continuity of care, efficiency of service, education of parents and patients, and patient satisfaction. 19 Single-center studies have shown that APPs can safely perform a range of procedures that were previously performed exclusively by physicians, such as thoracostomy insertion, 3 upper endoscopy, 4 and newborn circumcision. 5 In the immediate postoperative period, increased presence of APPs may help with early recognition of patients at risk of clinical deterioration and promote timely escalation of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a national survey of pediatric surgeons, nearly all respondents endorsed that integration of APPs in inpatient and outpatient settings positively impacted care, particularly with regard to continuity of care, efficiency of service, education of parents and patients, and patient satisfaction. 19 Single-center studies have shown that APPs can safely perform a range of procedures that were previously performed exclusively by physicians, such as thoracostomy insertion, 3 upper endoscopy, 4 and newborn circumcision. 5 In the immediate postoperative period, increased presence of APPs may help with early recognition of patients at risk of clinical deterioration and promote timely escalation of care.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the subject have focused thus far on relatively minor procedures performed within single centers. [3][4][5][6] Evidence from nonsurgical settings suggests that APPs may facilitate the delivery of care through enhanced care coordination and communication and by providing coverage in light of resident duty hour restrictions. 7 Task sharing may allow physicians to focus on patients with complex needs where advanced training may have a larger marginal impact on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Equally, endoscopy screening remains the preferred and essential intervention method for early diagnosis and treatment of bowel cancer and improved prognosis (Fang et al, 2014;Mendivil et al, 2019). Initially, the role of the ANP in gastroenterology nursing was largely associated with the performance of flexible sigmoidoscopy, but more recently has evolved to include diagnostic and therapeutic, upper and lower procedures (Baumgardner et al, 2017;Department of Nursing, 2020;Vance, 2005;Woods et al, 2006). Diagnostic procedures currently performed include gastroscopy, colonoscopy, and sigmoidoscopy while therapeutic procedures include polypectomy, biopsy, and stenting are undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed diagnosis, particularly of patients who received positive screening results and awaiting diagnostic endoscopy confirmation (Burch, 2020), coupled with increases in elective waiting lists and waiting times for endoscopy procedures, may result in health decline and ultimate succumbing to illness. Previous empirical studies associated with the role of the ANP in gastroenterology, focused largely on procedural safety and effectiveness of the role (Baumgardner et al, 2017;Bossa et al, 2006;Massl et al, 2014;Smale et al, 2003). Early randomised control trials (RCTs) concluded that experienced ANPs in gastroenterology can perform screening flexible sigmoidoscopy as safely and effectively as gastroenterologists (Schoenfeld et al, 1999).…”
Section: Introductionmentioning
confidence: 99%